1996
DOI: 10.1104/pp.112.4.1513
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Neutral and Alkaline Invertase from Carrot

Abstract: Neutral and alkaline invertase were identified in cells of a suspension culture of carrot (Daucus carota L.) and purified to electrophoretic homogeneity. Neutral invertase is an octamer with a molecular mass of 456 kD and subunits of 57 kD, whereas alkaline invertase is a tetramer with a molecular mass of 504 kD and subunits of 126 kD. Both enzymes had sharp pH profiles, with maximal activities at pH 6.8 for neutral invertase and pH 8.0 for alkaline invertase, and both hydrolyzed sucrose with typical hyperboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
10

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 35 publications
9
88
0
10
Order By: Relevance
“…At present, just why the sicy-192 mutant is recessive cannot be explained, although there is the following possibility. It has been reported that A/N invertase acts as homo-octamer or homo-tetramer in higher plants (41). Only when the holoenzyme consists of mutated subunits, will INV-E:C294Y become more stable.…”
Section: Discussionmentioning
confidence: 99%
“…At present, just why the sicy-192 mutant is recessive cannot be explained, although there is the following possibility. It has been reported that A/N invertase acts as homo-octamer or homo-tetramer in higher plants (41). Only when the holoenzyme consists of mutated subunits, will INV-E:C294Y become more stable.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline and neutral invertases are cytosolic and have neutral to weakly alkaline pH optima (Chen and Black, 1992;Van den Ende and Van Laere, 1995;Ross et al, 1996;Lee and Sturm, 1996). Alkaline and neutral invertases appear to be involved in the breakdown of sucrose to meet the metabolic demand for cytosolic hexoses (Ricardo, 1974;Masuda et al, 1988;Stommel and Simon, 1990; Lee and Sturm, 1996). cDNAs and genomic DNAs for soluble and cell wallbound acid invertases have been isolated from various plants (Sturm and Chrispeels, 1990;Arai et al, 1992;Klann et al, 1992;Elliott et al, 1993;Unger et al, 1994;Roitsch et al, 1995;Weber et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Both soluble and cell wall-bound invertases are involved in responses to wounding and pathogens (Matsushita and Uritani, 1974;Sturm and Chrispeels, 1990;Benhamou et al, 1991;Ohyama et al, 1995;Herbers et al, 1996;Zhang et al, 1996). Alkaline and neutral invertases are cytosolic and have neutral to weakly alkaline pH optima (Chen and Black, 1992;Van den Ende and Van Laere, 1995;Ross et al, 1996;Lee and Sturm, 1996). Alkaline and neutral invertases appear to be involved in the breakdown of sucrose to meet the metabolic demand for cytosolic hexoses (Ricardo, 1974;Masuda et al, 1988;Stommel and Simon, 1990; Lee and Sturm, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that alkaline invertase participates in the regulation of hexose and sucrose levels in the cytoplasm. For example, an increase in the concentration of glucose and fructose due to a decreased demand for hexoses would decrease sucrose metabolism directly through the inhibition of invertases (Lee & Sturm, 1996). We found that fructose and glucose inhibited rice alkaline invertase.…”
Section: mentioning
confidence: 66%
“…Ca# + and Mg# + had no effect on activity, whereas heavy metal ions, especially Hg# + , Cu# + and Ag + , decreased activity. Several reagents known to inhibit plant invertases (Karuppiah et al, 1989 ;Lin & Sung, 1993 ;Charng et al, 1994 ;Sung & Huang, 1994 ;Lee & Sturm, 1996) were tested (Table 2). At 5 mM, pyridoxine, pyridoxal, aniline and iodoacetamide decreased the activity to 40 %, 58 %, 30 % and 65 %, respectively.…”
Section: Effectorsmentioning
confidence: 99%